Reliability Analysis of Passenger Ship Structure Conversion in Bali Straits - Rizky Chandra Ariesta; Aries Sulisetyono; Totok Yulianto; Elwas Cahya Wahyu Pribadi (International Journal of Marine Engineering Innovation and Research, 2022)
LCT conversion passenger ships have been widely operated in the waters of the Bali Strait. Ship operations in the Bali Strait result in repeated loads on the structure. Repeated loading produces vertical and horizontal bending moments that act randomly due to waves. Based on this, it is necessary to analyze the structure of the ship. The purpose of this study was to analyze the reliability value of the ship structure operating in undulating waters. Wave analysis is performed using the spectral method to determine the value of the load acting on the ship, while the reliability calculation uses the Mean Value First Order Second Moment (MVFOSM) method to determine the reliability value. The analysis was carried out on a full load and an empty load. The value of the reliability of the structure at full load is 0.913615 and at empty load is 0.88948.